2011
DOI: 10.1063/1.3634046
|View full text |Cite
|
Sign up to set email alerts
|

Properties of the SiO2- and SiNx-capped GaAs(100) surfaces of GaInAsN/GaAs quantum-well heterostructures studied by photoelectron spectroscopy and photoluminescence

Abstract: SiO2 and SiNx layers are routinely deposited onto III-V(100) surfaces at different device processing steps. We elucidate these insulator-interface properties with photoemission and photoluminescence (PL) of SiO2- and SiNx-capped GaAs(100) surfaces of GaInAsN/GaAs quantum wells (QWs). Post-growth annealing led to an increase of the QW-PL intensity, of which origin can be clearly linked to the SiO2 and SiNx interfaces. Concomitantly, Ga2O–related photoemission increased, indicating useful formation of Ga2O at bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 25 publications
2
6
0
Order By: Relevance
“…Indeed, it has been previously confirmed that the PL intensity is sensitive to the properties of a thin oxide/III-V interface layer, and higher PL intensity corresponds to lower interface defect density. 1,[31][32][33][34] Therefore, the presented PL results prove that the defect density of the Al 2 O 3 /GaAs interface is reduced by using the pre-oxidized c(4 Â 2)-O layer. It is worth noting that the pure Al 2 O 3 /GaAs sample, used for the comparison, provides a stringent reference because a well-ordered GaAs starting surface, similar to that described previously, 34 was prepared before the ALD growth.…”
Section: Photoluminescence (Pl)supporting
confidence: 60%
“…Indeed, it has been previously confirmed that the PL intensity is sensitive to the properties of a thin oxide/III-V interface layer, and higher PL intensity corresponds to lower interface defect density. 1,[31][32][33][34] Therefore, the presented PL results prove that the defect density of the Al 2 O 3 /GaAs interface is reduced by using the pre-oxidized c(4 Â 2)-O layer. It is worth noting that the pure Al 2 O 3 /GaAs sample, used for the comparison, provides a stringent reference because a well-ordered GaAs starting surface, similar to that described previously, 34 was prepared before the ALD growth.…”
Section: Photoluminescence (Pl)supporting
confidence: 60%
“…This annealing induced surface damage is responsible for the significant current collapse phenomenon. It is known that Ga atoms tend to more easily diffuse into SiO 2 compared to SiN x [8]. Therefore, it is suggested that a SiN x film is a better choice as a protection layer for GaN surface during high temperature annealing.…”
Section: Methodsmentioning
confidence: 99%
“…Fitting of peaks arising from different chemical states or energy levels was done using CasaXPS software version 2.3.16 . Here, we focus on the curve fit analysis results of the high resolution As 3d peaks, since effects on Ga bonding have previously been investigated in detail . In our study, Ga 3d, that is commonly used for high resolution characterization of Ga chemical states could not be utilized due to highly intense tail from adjacent O 2s peak.…”
Section: Interface Analysismentioning
confidence: 99%
“…Indeed, the nature of these interface defects and the methods to control their formation have been the subject of a vast body of investigations (e.g., refs. ). In previous studies, these defect states have been found to arise, among others, from group‐V dimers; group‐V and group‐III dangling bonds; and III‐Ox or V‐Ox phases.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation